Adding Help to an HLA-A*24:02 Tumor-Reactive γδTCR Increases Tumor Control - Johanna, Inez; Hernández-López, Patricia; Heijhuurs, Sabine; Scheper, Wouter; Bongiovanni, Laura; de Bruin, Alain; Beringer, Dennis X.; Oostvogels, Rimke; Straetemans, Trudy; Sebestyen, Zsolt; Kuball, Jürgen (Frontiers in Immunology, 2021)
γδT cell receptors (γδTCRs) recognize a broad range of tumor antigens in mainly a major histocompatibility complex (MHC)-independent manner, making them valuable additions to the engineered immune effector cell therapy that currently focuses primarily on αβTCRs and chimeric antigen receptors (CARs). As an exception to the rule, we have previously identified a γδTCR, which exerts antitumor reactivity against HLA-A*24:02-expressing malignant cells, however without the need for defined HLA-restricted peptides, and without exhibiting any sign of off-target toxicity in humanized HLA-A*24:02 transgenic NSG (NSG-A24:02) mouse models. This particular tumor-HLA A*24:02-specific Vγ5Vδ1TCR required CD8αα co-receptor for its tumor reactive capacity when introduced into αβT cells engineered to express a defined γδTCR (TEG), referred to as TEG011, thus it was only active in CD8+ TEG011. We subsequently explored the concept of additional redirection of CD4+ T cells through co-transfer of the human CD8α gene into CD4+ and CD8+ TEG011 cells, later referred as TEG011_CD8α. Adoptive transfer of TEG011_CD8α cells in tumor-bearing humanized HLA A*24:02 transgenic NSG (NSG-A24:02) mice showed superior tumor control in comparison to TEG011, and to mock control groups. The total number of functional TEG011_CD8α cells persisted significantly longer in mice peripheral blood up to 4 weeks after TEG infusion, mainly due to a dominance of CD4+CD8+ double positive TEG011_CD8α which resulted in higher total counts of functional T cells in spleen and bone marrow. We observed that tumor clearance in the bone marrow of TEG011_CD8α-treated mice associated with better human T cell infiltration, which was not observed in the TEG011-treated group. Overall, introduction of transgenic human CD8α receptor on TEG011 improves antitumor reactivity against HLA-A*24:02+ tumor cells, and further enhances in vivo tumor control.